Influences of different components on viscosities of CaO-MgO-Al2O3-SiO2 melts - Zhang G.H.; Chou K.C.; Lv X.Y. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The present study is aimed to distinguish the different influences of CaO and MgO, as well as Al2O3 and SiO2 on viscosity of CaO-MgO-Al2O3-SiO2 melts. It is found that for melt without Al2O3, viscosity increases monotonously as CaO is gradually replaced by MgO. The addition of Al2O3 leads to a complex variation of viscosity. In different composition ranges, viscosity may exhibit different variation tendencies as changing the relative contents of CaO and MgO while keeping contents of other components constant. It is also found that when replacing SiO2 by equivalent mole of Al2O3, (i) in CaOAl 2O3-SiO2 system, viscosity increases when Al2O3 content is small relative to CaO content (there are enough Ca2+ ions to charge compensate Al3+ ions), but decreases when CaO content is inadequate for charge compensation; (ii) in MgO-Al2O3-SiO2 system, viscosity always decreases as substituting Al2O3 for SiO2. The reason for this difference for two systems may be resulted from the weak charge compensation ability of Mg2+ ion for Al3+ ion relative to Ca2+ ion. All the viscosity variations can be interpreted well by our new proposed viscosity model.